2012
DOI: 10.1002/jbm.a.34214
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells associated with porous chitosan–gelatin scaffold: A potential strategy for alveolar bone regeneration

Abstract: Tissue engineering has emerged as a novel treatment for replacement of lost bone tissue. This study evaluated the effects of a chitosan-gelatin scaffold seeded with bone marrow mesenchymal stem cells (BMMSCs) in the healing process of tooth sockets in rats. BMMSCs isolated from transgenic rats expressing enhanced green fluorescent protein (eGFP) were expanded and seeded on a chitosan-gelatin scaffold. These constructs were cultured for three days and characterized by scanning electronic microscopy (SEM) and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 41 publications
0
27
0
Order By: Relevance
“…Keywords: 27 Wound healing 28 Scar 29 Tissue engineering 30 Myofibroblasts 31 Paracrine signaling 32 3 3 a b s t r a c t 34 Currently available skin substitutes are still associated with a range of problems including poor engraft- 35 ment resulting from deficient vascularization, and excessive scar formation, among others. Trying to 36 overcome these issues, this work proposes the combination of poly(3-hydroxybutyrate-co-hydroxyvaler- 37 ate) (PHBV) structures with adipose-derived stem cells (ASCs) to offer biomechanical and biochemical 38 signaling cues necessary to improve wound healing in a full-thickness model.…”
mentioning
confidence: 99%
“…Keywords: 27 Wound healing 28 Scar 29 Tissue engineering 30 Myofibroblasts 31 Paracrine signaling 32 3 3 a b s t r a c t 34 Currently available skin substitutes are still associated with a range of problems including poor engraft- 35 ment resulting from deficient vascularization, and excessive scar formation, among others. Trying to 36 overcome these issues, this work proposes the combination of poly(3-hydroxybutyrate-co-hydroxyvaler- 37 ate) (PHBV) structures with adipose-derived stem cells (ASCs) to offer biomechanical and biochemical 38 signaling cues necessary to improve wound healing in a full-thickness model.…”
mentioning
confidence: 99%
“…In 83.33% of the studies in which scaffolds were compared, either with or without these components, the results showed a better regenerative performance with the presence of cells and/or growth factors. In other studies, there was no difference in results, neither with nor without bioactive factors [29, 56, 80], or there was no comparison between them [46, 62, 81]. Therefore, it cannot be asserted, from the results presented, that chitosan possesses per se activity that induces tissue regeneration, as some authors suggest [7, 10, 16, 22, 25].…”
Section: Discussionmentioning
confidence: 78%
“…In fact, some studies have clearly shown that the association of CS with collagen [42, 44, 68], silk fibroin [73], and HA [45, 57, 58] was capable of promoting greater tissue regeneration than pure CS, as in these studies pure or combined CS scaffolds were implanted, making it possible to establish a comparison between them. However, in the vast majority of studies evaluating CS combined with other biomaterials, the favorable results obtained cannot be attributed to the associations, as pure CS was neither evaluated nor used as a control [8, 30, 32, 41, 46, 48, 49, 53, 54, 62, 63, 67, 71, 76, 77, 80, 81, 83, 86, 88]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many carriers have been tested experimentally, using scaffolds composed of chitosan-gelatin blends 7 or bioactive glass showing biointegration and remodeling of tissues with features that allow for future applications 10,11 . This study assessed by CT imaging and histology, the ability to osteo-promotion of the association of biopolymer gel as carrier of bone morphogenetic protein and lyophilized bone grafts in the formation of a barrier compared to collagen membrane of bovine origin in the treatment of critical defects in rats calvarium in periods of 90 and 180 days after surgery.…”
Section: Introductionmentioning
confidence: 99%